Rosencrantz & Guildenstern Are Dead [videorecording (DVD)] - Stoppard, Tom; Oldman, Gary; Roth, Tim; Dreyfuss, Richard; Stoppard, Tom (2005)
The fringe characters from Shakespeare's 'Hamlet' take center stage at Elsinore.